The Effect of Transformational Leadership and Psychological Capital to Individual Readiness to Change for employees in Tourism Development Corporate - Ida Ayu Gede Hutri Dhara Sasmita (Universitas Katolik Soegijapranata, 2019)
This study aims to examine the effect of transformational leadership and psychological capital to individual readiness to change in tourism development corporate. Individual readiness to change measured by Readiness for Change, transformational leadership measured by Multifactor Leadership Questinnaire Form 5X—Short (MLQ Form 5X—Short), and psychological capital measured by Psychological Capital Quesionaire (PCQ). A quantitative survey was conducted on a probability sample of 127 employees in Tourism Development Corporate. The results of multiple regression showed that there is a positive correlation between transformational leadership and psychological capital to individual readiness to change.